Chinese One-shot Dilation versus Sequential Fascial Dilation for Percutaneous Nephrolithotomy: A Feasibility Study and Comparison - Xiong, Jing; Shi, Ying; Zhang, Xiaoping; Xing, Yifei; Li, Wencheng (Urology Journal, 2019)
Purpose: Nephrostomy tract creation is a key step to perform a successful percutaneous nephrolithotomy (PCNL). In an attempt to improve the conventional technique of the tract dilation, a Chinese one-shot dilation was developed and compared with the sequential fascial dilation. Materials and Methods: We retrospectively reviewed medical records of 116 patients who had undergone 116 PCNL in our department from January 2012 to December 2012. The nephrostomy tracts had been created by using Chinese one-shot (one-shot group, 59 cases) or sequential fascial dilation technique (sequential group, 57 cases). Tract creation time, hemorrhage loss, overall renal function, tract dilation failure and major complications were compared between the two groups. Results: The one-shot group had a significantly shorter mean (SD) tract creation time (1.9±0.4 vs 4.6±0.9 min, P<0.001) and lower mean (SD) decrease in hemoglobin concentration (0.59±0.32 vs 0.68±0.37 g/dL, P=0.0009) compared to the sequential group, respectively. There were no significant differences in mean (SD) value changes of pre- and post-operative serum creatine concentrations (4.6±11.3 vs 4.9±14.7 ?mol/L, P=0.259) between the one-shot and sequential group. No tract dilation failure or major complications occurred in both of the groups. Conclusion: This study demonstrated that the Chinese one-shot dilation technique is as safe and feasible as the conventional sequential fascial dilation. Furthermore, a greater reduction in tract creation time and blood loss was achieved using this technique.